THE APPLICATION OF GENERAL THEORY OF ROOT TRAJECTORIES METHODS IN RESEARCH OF MULTI-CHANNEL CONTROL SYSTEM WITH CROSS-CONNECTIONS - V. V. Tkachenko (Informatika, 2017)
Computer aided research method on the basis of general theory of root trajectories is considered in the frame of study of multi-channel control systems with varying parameters included as cofactors with arbitrary exponents in coefficients of the characteristic equation of the system. Possibilities of the method are demonstrated on the example of constructing stability regions projections on the plane of varying parameters of dual-channel pulse system with cross-connections.